Tumor-Associated Fibronectin Targeted Liposomal Nanoplatform for Cyclophilin A siRNA Delivery and Targeted Malignant Glioblastoma Therapy - Saw, Phei Er; Zhang, Ao; Nie, Yan; Zhang, Lei; Xu, Yingjie; Xu, Xiaoding (Frontiers in Pharmacology, 2018)
Malignant glioblastoma (GBM) is the most aggressive brain cancer that has a very low survival rate. With the rapid development of nanotechnology in the past few decades, the use of nanoparticles (NPs) for nucleic acid delivery is expected to have a revolutionary impact on GBM therapy. However, clinical success in GBM therapy remains a formidable challenge, mainly due to suboptimal in vivo delivery of therapeutics to glioma cells. Herein, we developed a new aptamer-like peptide (aptide)-decorated liposomal nanoplatform for systemic small interfering RNA (siRNA) delivery and targeted GBM therapy. This new nanoplatform is mainly composed of the following key components: 1) classic liposome structure with an aqueous core that can encapsulate therapeutic siRNA; ii) hydrophilic polyethylene glycol (PEG) chains on the outer shell to prolong blood circulation; and iii) surface-encoded aptide to specifically target the extra-domain B (EDB) of fibronectin that over-expressed on glioma cells. After systemic administration of these new siRNA delivery NPs, they can target the glioma cells and efficiently inhibit the GBM tumor growth by silencing the expression of cyclophilin A (CypA), which is up-regulated in brain cancer and plays an important role in malignant transformation of brain cancer and maintaining glioma cell stemness. These results suggest that the new RNA interference (RNAi) NP platform developed herein could become an effective tool for targeted GBM therapy.